2018
DOI: 10.4236/msce.2018.67007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Porous Carbon from Petroleum Pitch Using KOH

Abstract: Preparation and process optimization of porous carbons using different carbon sources and activating agents are frequently and commonly reported in open literature. However, only scanty references are made on utilization of petroleum coke for conversion to high surface area porous carbon using KOH as the activating agent. Hence, the present work attempts a process optimization exercise to prepare high surface area porous carbon from Petroleum coke using chemical activation (KOH) utilizing design of experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The author reported that the yields of APC obtained using K 2 CO 3 are 60% to 65%, the porosity development was higher and the surface area sharply increased than that obtained using KOH. The petroleum coke surface area and pore volume was increased using KOH activation, which was reported by Srinivaskannan et al The author reported that at 639°C, potassium hydroxide to coke ratio of 4.5 and 43 minutes activation, the surface area and yield was enhanced to 1765 m 2 /g and 89.8%. Yang et al studied N‐doped carbons prepared by ammonia combined with KOH activation.…”
Section: Introductionmentioning
confidence: 59%
“…The author reported that the yields of APC obtained using K 2 CO 3 are 60% to 65%, the porosity development was higher and the surface area sharply increased than that obtained using KOH. The petroleum coke surface area and pore volume was increased using KOH activation, which was reported by Srinivaskannan et al The author reported that at 639°C, potassium hydroxide to coke ratio of 4.5 and 43 minutes activation, the surface area and yield was enhanced to 1765 m 2 /g and 89.8%. Yang et al studied N‐doped carbons prepared by ammonia combined with KOH activation.…”
Section: Introductionmentioning
confidence: 59%
“…The image of AC0 sample derived from its precursor obtained by pyrolysis of pure VR shows large and small pore distribution and when compared with others, the pore development ws still not good yet because of the presence of denser structure in graphite layers. The appearance of white surface indicates that the presence of KOH that has not been removed perfectly during washing and neutralizing process [10]. The AC5, AC10, and AC15 corresponding to precursors prepared by co-pyrolysis of VR and gum rosin added 5, 10 and 15% weight of VR shows well developed pores, where there are differences in shapes and pore sizes.…”
mentioning
confidence: 99%